2018
DOI: 10.1002/jia2.25094
|View full text |Cite
|
Sign up to set email alerts
|

The Tablets, Ring, Injections as Options (TRIO) study: what young African women chose and used for future HIV and pregnancy prevention

Abstract: IntroductionPreventing HIV and unintended pregnancies are key global health priorities. To inform product rollout and to understand attributes of future multipurpose prevention technologies (MPT) associated with preference and use, we evaluated three placebo delivery forms: daily oral tablets, a monthly vaginal ring, and two monthly intramuscular injections in TRIO, a five‐month study among young Kenyan and South African women.Methods HIV‐negative, sexually active, non‐pregnant women aged 18 to 30 were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 24 publications
5
84
0
Order By: Relevance
“…Similarly, in a study where HIV negative, sexually active, non-pregnant women in Kenya and South Africa were randomized to receive either tablets, a monthly vaginal ring or intramuscular injection placebo delivery systems for multipurpose prevention of pregnancy and HIV, and subsequently given the choice of any delivery method, the participants expressed a preference for injectables above the other options. [ 22 ] The preference of oral pills observed in our study compared to other formulations of PrEP could be explained by lack of sufficient information with regards to the pros and cons of oral pills compared to parenteral formulations, and association of efficacy with HIV treatment formulations that are predominantly oral-based therapies. Also, the preference of oral pills observed in this study was different from that seen in the Voice-D (MTN-003D) study, with parenteral formulations being the most preferred among participants.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, in a study where HIV negative, sexually active, non-pregnant women in Kenya and South Africa were randomized to receive either tablets, a monthly vaginal ring or intramuscular injection placebo delivery systems for multipurpose prevention of pregnancy and HIV, and subsequently given the choice of any delivery method, the participants expressed a preference for injectables above the other options. [ 22 ] The preference of oral pills observed in our study compared to other formulations of PrEP could be explained by lack of sufficient information with regards to the pros and cons of oral pills compared to parenteral formulations, and association of efficacy with HIV treatment formulations that are predominantly oral-based therapies. Also, the preference of oral pills observed in this study was different from that seen in the Voice-D (MTN-003D) study, with parenteral formulations being the most preferred among participants.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies in African settings that assessed preferences among hypothetical or placebo PrEP products suggested that women’s acceptability of injectable products would be high, but that product choice and use patterns would also be shaped by individual and social context and geographies . Although a decision was made not to further evaluate TMC 278 LA as a prevention agent, in part due to requirements for cold‐chain storage, this study provides one of the first opportunities to examine acceptability of an injectable PrEP product among a geographically diverse group of women using an active product.…”
Section: Discussionmentioning
confidence: 99%
“…When longer durations of use (1 year) were proposed for the ring, the proportion stating the duration would be acceptable decreased. While there is some evidence that longeracting HIV prevention products, such as injections, are more favored by end-users [28][29][30][31][32], longer may not translate into better for the ring, as women may not want to leave the ring inserted beyond 1 month due to hygiene or comfort concerns. This nuance warrants closer examination in future research to determine the optimal duration for different products, as well as counseling around hygiene, acceptable intermittent removals for menses and other concerns, given that longer-acting products are currently in development [33].…”
Section: Discussionmentioning
confidence: 99%